Targeting TRAF6/IRF3 axis to inhibit NF-κB-p65 nuclear translocation enhances the chemosensitivity of 5-FU and reverses the proliferation of gastric cancer - Shitong Chen; Dong Zhang; Yi Du; Junbo Shi; Sikuan Gu; Xujun Zhou; Huijuan Yu; Feng Wang; Jinfei Chen; Hongjuan Cui (Cell Death and Disease)
Abstract Chemoresistance poses a significant clinical challenge in the treatment of gastric cancer (GC), while its underlying molecular mechanisms are still not fully understood. Post-translational protein modification and abnormal activation of nuclear factor-kappa B (NF-κB) are critical regulators of tumor chemoresistance. This study investigates the role of TNF receptors-associated factors 6 (TRAF6) in 5-Fluorouracil (5-FU) resistant GC. Utilizing short hairpin RNA (shRNA) to suppress TRAF6 expression in 5-FU resistant GC cells across both in vivo and in vitro models, we observed a marked reduction in cell proliferation and tumor growth. Low expression of TRAF6 inhibited nuclear translocation of NF-κB-p65, which was achieved by promoting the expression of Interferon regulatory factor 3 (IRF3). Importantly, TRAF6, an E3 ubiquitin ligase, bound to the IRF3-Δ (SR + IAD) (1-190aa) domain, inducing Lys70 ubiquitination of IRF3 to regulate its protein stability, with ubiquitin K48 residue playing a crucial role in this process. In conclusion, our study reveals the mechanism by which the TRAF6/IRF3 axis decreases GC’s cells sensitivity to 5-FU by promoting nuclear translocation of NF-κB-p65, offering valuable insights into overcoming chemoresistance in GC.